Effect of Vascular Photobiomodulation in the Postoperative Period of Alveolar Bone Grafting - Nicole Rosa de Freitas; Luisa Belluco Guerrini; Denise Sabbagh Haddad; Roberta Martinelli de Carvalho; Renato Yassutaka Faria Yaedú; Ana Lúcia Pompéia Fraga de Almeida (Dentistry Journal)
Background/Objectives: This study evaluated the effects of vascular photobiomodulation (VPBM) on pain intensity, edema, and facial temperature variation in patients undergoing alveolar bone grafting (ABG) surgery. Methods: A total of 42 patients with cleft lip and palate (aged 9–25 years) scheduled for ABG using iliac crest bone were randomly assigned in equal numbers (14 per group) to one of three groups: control (ABG only), test (ABG + VPBM), and placebo (ABG + simulated VPBM). Iliac and facial pain and edema were clinically evaluated 24 h post-surgery, along with thermographic facial analysis. Follow-up was conducted via phone calls for one week. Results: No statistically significant differences were observed among the groups regarding facial pain and edema at 24 h post-surgery. However, iliac pain significantly differed between the placebo and control groups (p = 0.045). A significant time-related effect on both facial and iliac pain outcomes was noted during follow-up, irrespective of the group. The need for rescue medication and self-perception of reduced edema did not differ significantly. Thermographic analysis reveals a significantly lower temperature variation in the test group (2.36 °C) compared to the other groups (p = 0.007). Conclusions: Overall, VPBM therapy influenced postoperative pain in the early recovery phase and temperature in the immediate postoperative period but did not significantly affect edema.